Senyawa Antidiabetes Fraksi Aktif Daun Ketapang (Terminalia catappa L.) - Hamsidar Hasan; Endah Nurrohwinta Djuwarno; Hasrita Samudi; Widy Susanti Abdulkadir; Faramita Hiola (State University of Gorontalo, 2022)
Antidiabetic is a compound that has a vital role in treating diabetes mellitus. Diabetes mellitus is a chronic metabolic disorder that is characterized by an increase in blood sugar levels. The use of traditional medicine is relatively cheaper and safer compared to synthetic drugs. One of the plants that is often used in traditional herbal medicine is ketapang (Terminalia catappa L.) because it contains a secondary metabolite compound that acts as an antidiabetic. Thus, this present study aimed to determine the n-hexane, ethyl acetate, and methanol extracts that had antidiabetic efficacy on blood sugar levels and compound group that acts as antidiabetic. The research employed mehods of multiple maceration, phytochemical screening, thin layer chromatography, and antidiabetic test, while the most effective antidiabetic efficacy was then continued to the fractionation stage using vacuum liquid chromatography and gravity column chromatography. Furthermore, the preparative thin layer chromatography (PTLC) analysi, UV-Vis zspectrometry and FTIR were carried out. The research findings revealed that the maximum wavelength of active fraction in ketapang (Terminalia catappa L.) leaves was 410.50 nm, and FTIR spectrum had functional groups of O-H (hydroxyl) C=O (carbonyl Co (aliphatic), C-O (ether) and CH3. Based on the finding, it could be concluded, that antidiabetic compound that plays a role in active fraction of ketapang (Terminalia Cappy L.) leaves was a flavonoid compound.